A Pengaruh Konsep Diri dan Kemandirian Belajar terhadap Pemahaman Konsep Matematika Siswa kelas XI di SMA Negeri 11 Medan - Siregar, Siti Hawa; Rajagukguk, Waminton (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2023)
The purpose of this study was to determine the effect of self-concept and learning independence on the understanding of mathematical concepts. This research is a correlational research with a quantitative approach. The population of this study were all 11th grade students at SMA Negeri Medan with the research sample being students of class XI IPA 4 and XI IPA 5 as many as 49 students who were taken by random sampling technique. The research instruments used were: Test of understanding mathematical concepts consisting of 8 questions; Self-concept questionnaire with 26 statement items; and Learning independence questionnaire with 27 statement items. The data analysis technique in this research is linear regression. The results and discussion of the research show: 1). Self-concept has a positive and significant effect on understanding of mathematical concepts; 2). Learning independence has a positive and significant effect on understanding of mathematical concepts; 3. Self-concept and learning independence together have a positive and significant effect on understanding mathematical concepts; and 4). The contribution of self-concept and learning independence simultaneously to the understanding of mathematical concepts result is 52,8%, while 47,2% are contributed by other factors.